Development Goals 2030: Teknologi Mudah Guna dalam Bimbingan dan Konseling - Kushendar, Kushendar; Lacksana, Indra; Permana, Nurul Enggar; Yunita, Reni (Kuras Institute, 2019)
The world development demands all aspect to develop particularly on education. In this era, the technology is needed especially for guidance and counseling in order to improve the services quality but did not substitute the core of guidance and counseling. The negative effect of technology used to be the jumping stone to do positive things. Therefore, the counselors should have the competence to improve technology, creative, innovative, and keep improving. Thus, the counselors will able to follow the world technology development.